INOVASI PEMBELAJARAN MAKHRIJUL HURUF HIJAIYAH MELALUI APLIKASI CANVA DI TADIKA AL FIKH ORCHARD TAMAN SETIA - Muhammad Raihan Setiawan; Mavianti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study was conducted at Taman Setia Tadika Al Fikh Orchad Malaysia and the study population amounted to 5 students. The pressing problem in this study is the discovery of the problem of students' pronunciation of hijaiyah letters which is still inaccurate due to the lack of knowledge about makharijul hijaiyah letters in accordance with the scientific rules of tajweed. This research uses a qualitative approach and case study design. This research aims to find out whether the Innovation of Learning Makhrijul Hijaiyah Letters Through Canva Application at Tadika Al Fikh Orchard Taman Setia. This study focuses on hijaiyah letters that are similar but different from makharijul letters. The results showed that 5 students of Tadika Al Fikh Orchard Taman Setia managed to pronounce the hijaiyah letters correctly after carrying out the learning of makharijul hijaiyah letters using the Canva application, therefore it can be concluded that the innovation of learning Makharijul Hijaiyah letters through the Canva application succeeded in increasing the speed of quality of learning Makharijul Hijaiyah letters at Tadika Al Fikh Orchard Taman Setia.